2020
DOI: 10.1097/ruq.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Axillary Ultrasound Helps in the Identification of a Limited Nodal Burden in Breast Cancer Patients

Abstract: Since the Z0011 trial, the clinical evaluation of axillary status has been redirected to predicting nodal tumor burden rather than nodal metastases. Our study aimed to evaluate the value of clinicopathological factors and axillary ultrasound (US) for the prediction of a high nodal burden (≥3 metastatic lymph nodes) in breast cancer patients. A total of 532 consecutive patients who underwent preoperative axillary US and subsequent surgery for clinical T1–2 breast cancer with a final pathologic analysis were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…In this analysis, high nodal burden group in IBC is associated with clinicopathological criteria, ultrasound characteristics, and tumor or ALN stiffness evaluated by SWE. LVI of the primary breast tumor is regarded as a well-known independent risk factor for axillary nodal metastases (16), the results of our research have shown that LVI has been correlated with an high nodal burden that confirms earlier issued articles (17,18), but the findings of LVI cannot be precisely provided until post-surgery pathology.…”
Section: Discussionsupporting
confidence: 78%
“…In this analysis, high nodal burden group in IBC is associated with clinicopathological criteria, ultrasound characteristics, and tumor or ALN stiffness evaluated by SWE. LVI of the primary breast tumor is regarded as a well-known independent risk factor for axillary nodal metastases (16), the results of our research have shown that LVI has been correlated with an high nodal burden that confirms earlier issued articles (17,18), but the findings of LVI cannot be precisely provided until post-surgery pathology.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the sensitivity and specificity of ABUS in predicting heavy nodal metastases were statistically similar to those of HHUS and those previously reported [ 17 24 ]. Among the diagnostic performance metrics, the NPV of ABUS was the highest, similar to that of HHUS and comparable to that previously reported (93%) by Luo et al [ 25 ]. This high NPV for heavy nodal burden metastases has implications in axillary management.…”
Section: Discussionsupporting
confidence: 89%